X-Git-Url: http://lambda.jimpryor.net/git/gitweb.cgi?a=blobdiff_plain;f=curry-howard.mdwn;h=183b54ebb463fb1cae33283053dc6703c15860dc;hb=HEAD;hp=6cd08c10de8cd1f8257bbdb1a2c82bef04adb3d8;hpb=fa3fcd726119256a230682b5125180daefd11235;p=lambda.git diff --git a/curry-howard.mdwn b/curry-howard.mdwn deleted file mode 100644 index 6cd08c10..00000000 --- a/curry-howard.mdwn +++ /dev/null @@ -1,322 +0,0 @@ -Curry-Howard, take 1 --------------------- - -We will return to the Curry-Howard correspondence a number of times -during this course. It expresses a deep connection between logic, -types, and computation. Today we'll discuss how the simply-typed -lambda calculus corresponds to intuitionistic logic. This naturally -give rise to the question of what sort of computation classical logic -corresponds to---as we'll see later, the answer involves continuations. - -So at this point we have the simply-typed lambda calculus: a set of -ground types, a set of functional types, and some typing rules, given -roughly as follows: - -If a variable `x` has type σ and term `M` has type τ, then -the abstract `\xM` has type σ `-->` τ. - -If a term `M` has type σ `-->` τ, and a term `N` has type -σ, then the application `MN` has type τ. - -These rules are clearly inverse of one another (in some sense to be -made precise): the functional types that abstract builds up are taken -apart by application. The intuition that abstraction and application -are dual to each other is the heart of the Curry-Howard -correspondence. - -The next step in making sense out of the Curry-Howard corresponence is -to present a logic. It will be a part of intuitionistic logic. We'll -start with the implicational fragment, that is, the part of -intuitionistic logic that only involves axioms and implications: - -
-Axiom: ---------
-        A |- A
-
-Structural Rules:
-
-          Γ, A, B, Δ |- C
-Exchange: ---------------------------
-          Γ, B, A, Δ |- C
-
-             Γ, A, A |- B
-Contraction: -------------------
-             Γ, A |- B
-
-           Γ |- B
-Weakening: -----------------
-           Γ, A |- B 
-
-Logical Rules:
-
-         Γ, A |- B
---> I:   -------------------
-         Γ |- A --> B  
-
-         Γ |- A --> B         Γ |- A
---> E:   -----------------------------------
-         Γ |- B
-
- -`A`, `B`, etc. are variables over formulas. -Γ, Δ, etc. are variables over (possibly empty) sequences -of formulas. Γ `|- A` is a sequent, and is interpreted as -claiming that if each of the formulas in Γ is true, then `A` -must also be true. - -This logic allows derivations of theorems like the following: - -
--------  Id
-A |- A
----------- Weak
-A, B |- A
-------------- --> I
-A |- B --> A
------------------ --> I
-|- A --> B --> A
-
- -Should remind you of simple types. (What was `A --> B --> A` the type -of again?) - -The easy way to grasp the Curry-Howard correspondence is to *label* -the proofs. Since we wish to establish a correspondence between this -logic and the lambda calculus, the labels will all be terms from the -simply-typed lambda calculus. Here are the labeling rules: - -
-Axiom: -----------
-       x:A |- x:A
-
-Structural Rules:
-
-          Γ, x:A, y:B, Δ |- R:C
-Exchange: -------------------------------
-          Γ, y:B, x:A, Δ |- R:C
-
-             Γ, x:A, x:A |- R:B
-Contraction: --------------------------
-             Γ, x:A |- R:B
-
-           Γ |- R:B
-Weakening: --------------------- 
-           Γ, x:A |- R:B     [x chosen fresh]
-
-Logical Rules:
-
-         Γ, x:A |- R:B
---> I:   -------------------------
-         Γ |- \xM:A --> B  
-
-         Γ |- f:(A --> B)      Γ |- x:A
---> E:   -------------------------------------
-         Γ |- (fx):B
-
- -In these labeling rules, if a sequence Γ in a premise contains -labeled formulas, those labels remain unchanged in the conclusion. - -What is means for a variable `x` to be chosen *fresh* is that -`x` must be distinct from any other variable in any of the labels -used in the (sub)proof up to that point. - -Using these labeling rules, we can label the proof -just given: - -
-------------  Id
-x:A |- x:A
----------------- Weak
-x:A, y:B |- x:A
-------------------------- --> I
-x:A |- (\y.x):(B --> A)
----------------------------- --> I
-|- (\x y. x):A --> B --> A
-
- -We have derived the *K* combinator, and typed it at the same time! - -In order to make use of the dual rule, the one for `-->` elimination, -we need a context that will entail both `A --> B` and `A`. Here's -one, first without labels: - -
-------------------Axiom          
-A --> B |- A --> B          
----------------------Weak        ---------Axiom
-A --> B, A |- A --> B              A |- A
----------------------Exch        -----------------Weak 
-A, A --> B |- A --> B              A, A --> B |- A
--------------------------------------------------- --> E
-A, A --> B |- B 
-
- -With labels, we have - -
-------------------------Axiom          
-f:A --> B |- f:A --> B          
-----------------------------Weak        -------------Axiom
-f:A --> B, x:A |- f:A --> B              x:A |- x:A
-----------------------------Exch        ------------------------Weak 
-x:A, f:A --> B |- f:A --> B              x:A, f:A --> B |- x:A
--------------------------------------------------------------- --> E
-x:A, f:A --> B |- (fx):B 
-
- -Note that in order for the `--> E` rule to apply, the left context and -the right context (the material to the left of each of the turnstiles) -must match exactly, in this case, `x:A, f:A --> B`. - -At this point, an application to natural language will help provide -insight. -Instead of labelling the proof above with the kinds of symbols we -might use in a program, we'll label it with symbols we might use in an -English sentence. Instead of a term `f` with type `A --> B`, we'll -have the English word `left`; and instead of a term `x` with type `A`, -we'll have the English word `John`. - -
------------------------------Axiom          
-left:e --> t |- left:e --> t          
---------------------------------------Weak        -------------------Axiom
-left:e --> t, John:e |- left:e --> t              John:e |- John:e
---------------------------------------Exch        --------------------------------Weak 
-John:e, left:e --> t |- left:e --> t              John:e, left:e --> t |- John:e
----------------------------------------------------------------------------------- --> E
-John:e, left:e --> t |- (left John):t 
-
- -This proof illustrates how a logic can -provide three things that a complete grammar of a natural language -needs: - -* It characterizes which words and expressions can be combined in -order to form a more complex expression. For instance, we've -just seen a proof that "left" can combine with "John". - -* It characterizes the type (the syntactic category) of the result. -In the example, an intransitive verb phrase of type `e --> t` combines -with a determiner phrase of type `e` to form a sentence of type `t`. - -* It characterizes the semantic recipe required to compute the meaning - of the complex expression based on the meanings of the parts: the - way to compute to meaning of the expression "John left" is to take - the function denoted by "left" and apply it to the individual - denoted by "John", viz., "(left John)". - -This last point is the truly novel and beautiful part, the part -contributed by the Curry-Howard result. - -[Incidentally, note that this proof also suggests that if we have the -expressions "John" followed by "left", we also have a determiner -phrase of type `e`. If you want to make sure that the contribution of -each word counts (no weakening), you have to use a resource-sensitive -approach like Linear Logic or Type Logical Grammar. - -In this trivial example, it may not be obvious that anything -interesting is going on, so let's look at a slightly more complicated -example, one that combines abstraction with application. - -Linguistic assumptions (abundently well-motivated, but we won't pause -to review the motivations here): - -Assumption 1: -Coordinating conjunctions like *and*, *or*, and *but* require that -their two arguments must have the same sytnactic type. Thus we can -have - -
-1. [John left] or [Mary left]     coordination of t 
-2. John [left] or [slept]         coordination of e -> t
-3. [John] or [Mary] left          coordination of e
-etc.
-
-4. *John or left.
-5. *left or Mary slept.
-etc.
-
- -If the two disjuncts have the same type, the coordination is perfectly -fine, as (1) through (3) illustrate. But when the disjuncts don't -match, as in (4) and (5), the result is ungrammatical (though there -are examples that may seem to work; each usually has a linguistic -story that needs to be told). - -In general, then, *and* and *or* are polymorphic, and have the type -`and:('a -> 'a -> 'a)`. In the discussion below, we'll use a more -specific instance to keep the discussion concrete, and to abstract -away from polymorphism. - -Assumption 2: -Some determiner phrases do not denote an indivdual of type `e`, and -denote only functions of a higher type, typically `(e -> t) -> t` (the -type of an (extensional) generalized quantifier). So *John* has type -`e`, but *everyone* has type `(e -> t) -> t`. - -[Excercise: prove using the logic above that *Everyone left* can have -`(everyone left)` as its Curry-Howard labeling.] - -The puzzle, then, is how it can be possible to coordinate generalized -quantifier determiner phrases with non-generalized quantifier -determiner phrases: - -1. John and every girl laughed. -2. Some boy or Mary should leave. - -The answer involves reasoning about what it means to be an individual. - -Let the type of *or* in this example be `Q -> Q -> Q`, where -`Q` is the type of a generalized quantifier, i.e, `Q = ((e->t)->t`. - -John:e |- John:e, or:(Q->Q->Q) |- , everyone:Q, left:e->t - -
------------------Ax  -----------------Ax
-John:e |- John:e     P:e->t |- P:e->t
---------------------------------------Modus Ponens (proved above)
-John:e, P:e->t |- (P John):t
---------------------------------- --> I
-John:e |- (\P.P John):(e->t)->t
-
- -This proof is very interesting: it says that if *John* has type `e`, -then *John* automatically can be used as if it also has type -`(e->t)->t`, the type of a generalized quantifier. -The Curry-Howard labeling is the term `\P.P John`, which is a function -from verb phrase meanings to truth values, just as we would need. - -[John and everyone left] - -beta reduction = normal proof. - - - -[To do: add pairs and destructors; unit and negation...] - -Excercise: construct a proof whose labeling is the combinator S, -something like this: - - --------- Ax --------- Ax ------- Ax - !a --> !a !b --> !b c --> c - ----------------------- L-> -------- L! - !a,!a->!b --> !b !c --> c ---------- Ax ---------------------------------- L-> -!a --> !a !a,!b->!c,!a->!b --> c ------------------------------------------- L-> - !a,!a,!a->!b->!c,!a->!b --> c - ----------------------------- C! - !a,!a->!b->!c,!a->!b --> c - ------------------------------ L! - !a,!a->!b->!c,! (!a->!b) --> c - ---------------------------------- L! - !a,! (!a->!b->!c),! (!a->!b) --> c - ----------------------------------- R! - !a,! (!a->!b->!c),! (!a->!b) --> !c - ------------------------------------ R-> - ! (!a->!b->!c),! (!a->!b) --> !a->!c - ------------------------------------- R-> - ! (!a->!b) --> ! (!a->!b->!c)->!a->!c - --------------------------------------- R-> - --> ! (!a->!b)->! (!a->!b->!c)->!a->!c